คุณภาพชีวิตผู้สูงอายุตำบลดูนสาด อำเภอกระนวน จังหวัดขอนแก่น - และคณะ, ศิริประภา วงค์ประพันธ์ (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2019)
This research has the aims to study: 1) the elderly quality of life in Doonsart sub-district, Kranuan district, Khonkaen province, 2) the suggestions to develop the elderly quality of life in Doonsart sub-district, Kranuan district, Khonkaen province. The researcher collected the data from 282 sampling respondents by using the questionnaires, and analyzed the data by percentage, mean,and standard deviation statistics. The result was as follows: The overall elderly quality of life in Doonsart sub - district, Kranuan district, Khonkaen province was at highest mean level 1) the aspect of physical condition 2) the aspect of psychological condition 3) the aspect of communal relation and 4) the aspect of environment. There were 4 suggestions from this study; 1) the elders should exercise every day, 2) the official should provide the psychiatrists for the elders, 3) the official and the community should support the elders to participate community activities, and 4) the official should provide recreational place for the elders. Keywords: Elderly, Quality of life